Pili of Neisseria meningitidis: effect of media on maintenance of piliation, characteristics of Pili, and colonial morphology. - McGee, Z A (1979)
In contrast to information in the literature which indicates that meningococci rapidly lose pili upon cultivation in vitro, we found that piliation of meningococci could be maintained in vitro for 15 or more passages. Pili were present on all eight isolates tested, whether from asymptomatic carriers or from subjects with meningococcal disease. Complete loss of piliation occurred in the same two strains on two of the three media tested. On one medium (Thayer-Martin medium with supplement B), there was partial or complete loss of pili by all strains. The optimal medium for maintaining pili was chocolate agar with 1% IsoVitaleX; 95% or more of the microorganisms of six of the eight strains tested were piliated after 15 passages in vitro, and more than 60% of the microorganisms of the other two strains were piliated. Meningococci passed on this medium generally maintained their initial density of piliation (3 to 34 pili per diplococcus). The ability to predictably cultivate piliated meningococci in vitro and to select piliated and nonpiliated clones of the same strain should allow investigation of the biochemical and immunological properties of meningococcal pili as well as their possible role in the pathogenicity of Neisseria meningitidis.